749 Is daytime sleepiness a risk factor for depression and the prevalence of depression in patients with EDS referred for PSG. (3rd May 2021) - Pervaiz, Hassan; Roth, Heidi; Vaughn, Bradley
Abstract: Introduction: Excessive daytime sleepiness affects 18.9–27% of the general population. [1] Patients with excessive daytime sleepiness have a higher prevalence of major depressive episodes. [2] Depression is also associated with poor medical compliance which may further affect management of excessive day time sleepiness. [3] We therefore are interested in the prevalence of depression in patients undergoing in-lab testing for excessive sleepiness and the association of positive depression screening. Methods: Retrospective review of diagnostic polysomnograms (PSG) in a tertiary care facility was conducted on patients over 18 years of age. The elements collected include: gender, age, BMI, Depression scale defined by PHQ-9, EDS defined by Epworth's Sleepiness scale, AHI = Apnea Hypopnea Index, PLMS = Periodic Limb Movements in Sleep. Results: There were a total of 32 subjects. Median age was 49 with 43% male and average BMI of 35. The mean PHQ-9 score was 5.8. The mean Epworth score was 8.5. The correlation of the two values was r= 0.078. 12 patients are classified as having EDS. 7 patients (58.3%) in the EDS group were positive for depression screen. 18 patients (90%) without EDS were positive for depression screen. There is no statistical difference 2 groups (58.3% vs 90%, p=1). The mean PHQ-9 score in EDS group is 5.5. The mean PHQ-9 score in non EDS group is 5.95. There is no statistical difference between 2 groups PHQ-9(5.5 vs 5.95, p=0.779). Conclusion: Our study cohort did not find a correlation between subjective sleepiness and depression in individuals presenting for in lab polysomnography. This may be related to the sample size or be an indication that many other factors contribute to the sleepiness in this cohort. Support (if any): 1. Hein M. et al (2019) Prevalence and risk factors of excessive daytime sleepiness in major depression: A study with 703 individuals referred for polysomnography. J Affect Disord. 2. Chellappa SL. et al (2006) Excessive daytime sleepiness in patients with depressive disorder. Braz J Psychiatry. 3. Grenard JL et al (2011) Depression and medication adherence in the treatment of chronic diseases in the United States: a meta-analysis. J Gen Intern Med